Global research landscape of cactus pear (Opuntia ficus-indica) in agricultural science - Naorem, Anandkumar; Patel, Abhishek; Hassan, Sawsan; Louhaichi, Mounir; Jayaraman, Somasundaram (Frontiers in Sustainable Food Systems, 2024)
The cultivation of unconventional or underutilized crops, such as Opuntia ficus-indica (OFI), under a climate change scenario is an important subject and has been increasingly studied in agricultural research. Therefore, a scientometric study was conducted to identify research focal points, assess the milestones that have been attained (1990–2023), determine the extent of progress made, and outline possible directions in this field. Using the Web of Science database, the study identified 2,372 OFI documents that were refined into 518 research articles in English related to agriculture. The increase in publications showed a more pronounced acceleration after 2000. On average, each OFI research document had five co-authors, with 17.6% involving international collaboration among 1,835 authors. The analysis revealed that the OFI has gained prominence as an agronomic resource in regions characterized by a severe drought, which has prompted a surge in physiological investigations focused on cladodes aimed at comprehending its crassulacean acid metabolism capability, which contributes to reduced transpiration and higher water use efficiency than other conventional crops. Furthermore, there has been an increase in research on animal health and nutrition, pest and disease control, and climate-smart OFI characteristics. We would emphasize the importance of research on standardization of agronomic practices based on local climate, the role of OFI in climate change, biofuel, taxonomy, stress tolerance, cultivar selection, wildlife interference, animal health/nutrition, economic studies, soil quality, and pest control. By addressing the identified research gaps and pursuing the suggested paths, the rope can be strengthened in sustainable agriculture, food security, and environmental management.